Training On Improving Early Detection And Management Of Sepsis: Education On The Use Of Biomarkers And Clinical Parameters For Health Care Workers - Rahmat, Rosyadi Aziz (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Sepsis is a systemic syndrome that results from an infection that causes an uncontrolled inflammatory response in the body. This inflammatory response can lead to tissue damage, organ dysfunction and even multiple organ failure. Sepsis can progress to septic shock, a condition where blood pressure is extremely low and fails to recover despite fluid administration. In Indonesia, sepsis is also a serious health problem, with prevalence increasing along with the development of infectious diseases. A study in Indonesian hospitals showed that sepsis is the leading cause of death in the intensive care unit (ICU). The incidence rate of sepsis in Indonesia is estimated to range between 10-20% of patients admitted to the ICU. Sepsis is a leading cause of death in hospitals, especially if not detected or treated quickly. Approximately 30-50% of patients with severe sepsis or septic shock will die if they do not receive appropriate treatment. Based on the data obtained from the pre-test and post-test, it can be seen that there is a significant improvement in the understanding and skills of health workers, which reflects the success of the training conducted. In the pre-test, the average comprehension score of the participants was 55%, while after the training it increased to 80%. With the application of knowledge about biomarkers and clinical parameters, early detection of sepsis is significantly improved.